Genomic analysis, simultaneous production, and process optimization of extracellular polymeric substances and polyhydroxyalkanoates by Methylobacterium sp. ISTM1 by utilizing molasses. (June 2022) - Tyagi, Bhawna; Gupta, Bulbul; Khatak, Deepak; Meena, Ramovatar; Shekhar Thakur, Indu
Highlights: EPS and PHA were produced simultaneously by Methylobacterium sp . ISTM1. Genes related to EPS and PHA production were revealed by whole-genome sequencing. 7.18 g L -1 EPS and 1.41 g L -1 PHA were produced by ISTM1 at 9% molasses, pH 7. Both the EPS and PHA were subjected to cytotoxicity assay and were found non-toxic. Abstract: In the current study, the isolated Methylobacterium sp. ISTM1 simultaneously produced both extracellular polymeric substances (EPS) and polyhydroxyalkanoates (PHA) in a single-step process. The yield of biopolymers (EPS and PHA) was enhanced by optimizing the process parameters of EPS and PHA production. Methylobacterium sp. ISTM1 was able to produce 7.18 ± 0.04 g L -1 EPS and 1.41 ± 0.04 g L -1 PHA simultaneously at optimized culture conditions i.e., 9% molasses and pH 7. The genomic analysis of the strain has identified the involved genes and pathways in the production of EPS and PHA. Both the biopolymers were found non-toxic according to the cytotoxicity analysis. The results of the current study present the potential of the bacterium Methylobacterium sp. ISTM1 produces non-toxic biopolymers by utilizing agro-industrial waste (molasses) that can be harnessed sustainably for various applications.